From Accounting Information to Institutional Accountability: A Comparative Documentary Analysis of Indonesian Universities - Ade Kemala Jaya (Universitas Riau Kepulauan, 2026)
Purpose: This study examines how accounting information disclosed by Indonesian universities can be traced into institutional performance and accountability. It responds to the limitation of disclosure-oriented approaches that assess whether financial information is available without examining whether the information can be connected to institutional objectives, performance, deviations, and management response. Design/methodology/approach: A comparative documentary analysis was conducted using publicly accessible institutional documents from Universitas Negeri Yogyakarta, Universitas Indonesia, Universitas Hasanuddin, and Universitas Muhammadiyah Jakarta. Annual reports, financial reports, performance reports, budget and realization information, strategic documents, and financial-management disclosures were analyzed through an Accounting-to-Accountability Traceability (AAT) lens. The analysis distinguishes management accounting information, traceability between resources and performance, and observable accountability evidence. Findings: The four universities disclose substantial accounting and financial-management information, but the extent to which that information forms an observable accountability chain differs. Four dominant documentary pathways were identified: audit–performance traceability, budget–realization–deviation traceability, planning–budget–performance traceability, and financial-control infrastructure. The findings indicate that disclosure alone does not establish accountability; traceability becomes stronger when accounting information is explicitly connected to resource allocation, performance, variance, explanation, and management response. Practical implications: Universities and higher education regulators should move from disclosure-oriented financial reporting toward traceability-oriented accountability reporting by linking budget, realization, performance, variance, explanation, and follow-up. Originality/value: The study contributes an Accounting-to-Accountability Traceability perspective that treats accounting information not merely as a reporting output, but as a mechanism through which resource use can be followed into institutional performance and accountability.